Posición del ministerio público para determinar la pena concreta ante la coexistencia de causales de disminución de punibilidad y circunstancias agravantes cualificadas en los procesos penales en la provincia de Maynas, periodo 2021–2023 - Estrella Tafur, Karolen (2024)
This research investigates whether in criminal proceedings in the province of Maynas during the period 2021-2023, in the presence of both a cause for reduction of punishment and a qualified aggravating circumstance, the Public Prosecutor's Office determines the specific penalty according to national jurisprudence. The main objective is to determine the criteria applied by the Public Prosecutor's Office to individualize the penalty in such cases, in accordance with national jurisprudence. The research is based on a basic approach, using theoretical, doctrinal, and jurisprudential knowledge to address the research question. The research design is non-experimental - transactional, with no manipulation of variables, and the method used is quantitative, including measurement and descriptive statistics of relevant variables. Findings indicate that in criminal proceedings in the province of Maynas during the mentioned period, the Public Prosecutor's Office does not consistently follow national criminal jurisprudence when faced with a punitive scenario involving both concurrent conditions. This inconsistency arises from the lack of a uniform line in national criminal jurisprudence, resulting in divergent criteria that significantly impact legal certainty. This situation negatively affects judicial operators, who adopt different jurisprudential positions for similar cases, thereby creating uncertainty in the application of the law.